Effects of Aerobic Exercise Alone on Lipids in Healthy East Asians: A Systematic Review and Meta-Analysis - Akazawa, Nobuhiko; Igarashi, Yutaka; Maeda, Seiji (Journal of Atherosclerosis and Thrombosis, 2019)
Aim: The purpose of the current work was to review the effects of regular aerobic exercise on serum lipid and lipoprotein levels in East Asians using meta-analysis. Methods: The randomized controlled trials analyzed involved healthy adults who were East Asians with a mean age ≥40 years, an exercise group that only performed regular aerobic exercise, and a control group that did not carry out exercise-related intervention; the trials indicated mean high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), or triglyceride (TG). The mean difference (MD) was defined as the difference (mean value at post-intervention in the exercise group－mean value at baseline in the exercise group)－(mean value at post-intervention in the control group－mean value at baseline in the control group) in HDL-C, LDL-C, TC, and TG and was calculated for each trial. The weighted MD was calculated with a random-effects model. Results: The meta-analysis examined 994 subjects in 25 studies. The weighted MD in HDL-C, TC, and TG improved significantly (HDL-C, 2.2 mg/dL; TC, －5.8 mg/dL; TG, －13.7 mg/dL). The weighted MD in HDL-C and TC contained significant heterogeneity (HDL-C, I2＝45.1%; TC, I2＝56.2%). When trials were limited to those involving moderate-intensity exercise (55%–69% of the maximum heart rate) or an exercise volume ≥150 min/week, the weighted MD in HDL-C, LDL-C, TC, and TG improved significantly and did not contain significant heterogeneity.Conclusions: The findings suggest that the ideal form of exercise to improve lipid and lipoprotein levels in East Asians is exercise of moderate-intensity and in a volume ≥150 min/week.